Quartic Sum Determination

Algebra Level 4

x 3 8 x 2 + 5 x + 12 = 0 \large x^3-8x^2+5x+12 = 0

If A , B A,B and C C are roots of the equation above, find the value of A 4 + B 4 + C 4 A^4 + B^4+C^4 .


The answer is 2482.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Danish Ahmed
Aug 8, 2015

Equating coefficients in

( x A ) ( x B ) ( x C ) = x 3 8 x 2 + 5 x + 12 (x - A)(x - B)(x - C) = x^3 - 8x^2 + 5x + 12 gives:

A + B + C = 8 A + B + C = 8

A B + B C + C A = 5 AB + BC + CA = 5

A B C = 12. ABC = -12.

Using these values in the following identity:

A 4 + B 4 + C 4 = ( A + B + C ) 4 4 ( A + B + C ) 2 ( A B + B C + C A ) + 2 ( A B + B C + C A ) 2 + 4 A B C ( A + B + C ) A^4 + B^4 + C^4 = (A + B + C)^4 - 4(A + B + C)^2(AB + BC + CA) +2(AB + BC + CA)^2 + 4ABC(A + B + C)

A 4 + B 4 + C 4 = 84 4 82 5 + 2 52 4 12 8 = 2482 A^4 + B^4 + C^4 = 84 - 4*82*5 + 2*52 - 4*12*8 = 2482

Moderator note:

Your identity for A 4 + B 4 + C 4 A^4+B^4+C^4 is not commonly known. How did you come up with that?

Alternatively, there's a simpler approach.

Hint 1 : Newton's Sum. Or Newton's identity.

Hint 2 : A 2 + B 2 + C 2 = ( A + B + C ) 2 2 ( A B + A C + B C ) A^2 + B^2+ C^2 = (A+B+C)^2-2(AB+AC+BC) .

the solution comes from newton binomials, right??

WeiLiang Wu - 5 years, 10 months ago
Ben Habeahan
Sep 2, 2015

you can read newton identities

here.

Let P 1 = A + B + C , P 2 = A B + B C + C A , P 3 = A B C , P_1=A+B+C, \\ P_2=AB+BC+CA , \\ P_3=ABC,

with vieta's formula P 1 = 8 , P 2 = 5 , P 3 = 12. P_1=8, P_2=5, P_3=-12.

Using newton identities, we have: S 1 = P 1 = 8 S 2 = P 1 S 1 2 P 2 = ( 8 ) ( 8 ) 2 ( 5 ) = 54 S 3 = P 1 S 2 P 2 S 1 + 3 P 3 = ( 8 ) ( 54 ) ( 5 ) ( 8 ) + ( 3 ) ( 12 ) = 356 S 4 = P 1 S 3 P 2 S 2 + P 3 S 1 = ( 8 ) ( 356 ) ( 5 ) ( 54 ) + ( 12 ) ( 8 ) = 2482 S_1=P_1=8 \\ S_2=P_1S_1-2P_2=(8)(8)-2(5)=54 \\ S_3=P_1S_2-P_2S_1+3P_3=(8)(54)-(5)(8)+(3)(-12)=356 \\ S_4=P_1S_3-P_2S_2+P_3S_1=(8)(356)-(5)(54)+(-12)(8)= \boxed{2482}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...